تأثير أنظمة مختلفة من الحراثة في نمو الشعير المزروع بعلاً ، وإنتاجيته، في ظروف المنطقة الساحلية. - سلامة, سليمان; ميهوب, علي; جراد, سمير (Latakia University Journal -Biological Sciences Series, 2013)
أجري البحث في مزرعة فديو التابعة لكلية الزراعة بجامعة تشرين خلال الموسمين الزراعيين 2008-2009 و2009-2010م. واستخدم في البحث مجموعة من نظم الحراثة المختلفة لزراعة الشعير . أظهرت نتائج البحث تأثيراً ملحوظاً لنظم الحراثة في الكثافة الظاهرية للتربة، حيث زادت الكثافة الظاهرية في المعاملة الأولى (من دون حراثة) قياساً ببقية المعاملات، التي كانت جميعها أقل منها. وقل عدد الأعشاب الضارة في المعاملة التي اجريت فيها حراثة صيفية بالمحراث المطرحي القلاب + حراثة بالمحراث الحفار والتمشيط قبل الزراعة. كما لوحظ أن لنظم الحراثة تأثيراً ملحوظاً في نسبة الإنبات حيث كانت نسبة الانبات في المعاملة التي اجريت فيها حراثة صيفية بالمحراث المطرحي القلاب + حراثة بالمحراث الحفار والتمشيط قبل الزراعة أفضل ما يمكن قياساً بالنظم الأخرى. وقل وزن الـ 1000 حبة والإنتاجية/هـ عند اتباع نظام اللاحراثة، قياساً ببقية أنظمة الحراثة الأخرى المتبعة. أما أقل كثافة ظاهرية للتربة فكانت عند استخدام المعاملة التي أجريت فيها حراثة صيفية بالمحراث القرصي+حراثة بالمحراث الحفار والتمشيط قبل الزراعة، وقل عدد الأعشاب وارتفعت نسبة الإنبات وزاد وزن الـ 1000 حبة عند اتباع المعاملة السادسة. أما الإنتاجية فقد كانت أكبر عند استخدام المعاملة السادسة أيضاً. وبحساب الجدوى الاقتصادية تبين أن استخدام نظام اللاحراثة (الشاهد) أعطى أفضل جدوى اقتصادية حيث كانت كلفة الكغ الواحد (11.19 ل.س في المتوسط لعامي التجربة)، أما أكبر كلفة لإنتاج الكغ الواحد فكانت في المعاملة التي أجريت فيها حراثة صيفية بالمحراث القرصي+حراثة بالمحراث الحفار والتمشيط قبل الزراعة، حيث بلغت كلفة الكغ الواحد 16.40 ل.س في المتوسط لعامي التجربة. <!--[if gte mso 9]> 800x600 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The research was carried out during (2008-2009) and (2009-2010) in Fedio farm belonging to the Faculty of Agriculture to study the effect of various systems of tillage on the growth and productivity of Barley. The results showed that the bulk density increases with the first tillage system (control), comparing with the other tillage systems, but all of them were less than the control (no- tillage). The number of weeds increased when using the 6-th tillage system. The germination rate was affected by the tillage systems. The 6-th tillage system was the best. The weight of 1000 seeds and productivity increased by the 1-th tillage system (no-tillage) comparing with the other tillage systems. The number of weeds increased, but germination rate and weight of 1000 seeds decreased by using the 6-th tillage system. The yield of barley increased when using the 6-th tillage system. No-tillage system was the most economic compared with the others <!--[if gte mso 9]> 800x600 <![endif]--> Effect of Various Systems of Tillage on Growth and Productivity of Rainfed Barley (Hordium sativum.L) in the Coastal Area. <!--[if gte mso 9]> 800x600 <![endif]--> The research was carried out during (2008-2009) and (2009-2010) in Fedio farm belonging to the Faculty of Agriculture to study the effect of various systems of tillage on the growth and productivity of Barley. The results showed that the bulk density increases with the first tillage system (control), comparing with the other tillage systems, but all of them were less than the control (no- tillage). The number of weeds increased when using the 6-th tillage system. The germination rate was affected by the tillage systems. The 6-th tillage system was the best. The weight of 1000 seeds and productivity increased by the 1-th tillage system (no-tillage) comparing with the other tillage systems. The number of weeds increased, but germination rate and weight of 1000 seeds decreased by using the 6-th tillage system. The yield of barley increased when using the 6-th tillage system. No-tillage system was the most economic compared with the others<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->